Hubungan Tingkat Kebugaran Jasmani terhadap Hasil Belajar PJKR Siswa Kelas XI MA Negeri 1 Kepulauan Meranti - Rofi Wahid Fahrozi; Agus Sulastio; Wedi S; Oca Fernandes AF (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2025)
Physical Education is part of overall education which prioritizes physical activity and to realize this there are many ways carried out by the government, for example sports coaching and Physical Education in schools. The function and objectives of the education system illustrate that physical education and sports are one of the factors that can help in improving the quality of national education. Therefore, physical education needs to be implemented well and consistently starting from elementary school, junior school, high school and university. This assessment aims to determine the relationship between the level of physical fitness and the learning outcomes of class XI students at MA Negeri 1 Meranti Islands. The type of research used is quantitative descriptive research. The subjects of this research were 30 students in Senior High School. The data analysis technique in this research uses descriptive statistical techniques with significant product moment correlation tests. Data analysis used in this research uses descriptive analysis techniques with average values. The results of data processing using manual calculations and the SPSS program obtained several categories of physical fitness levels, namely very good (10%), good (73.33%), fair (16.67%), poor (0%), and very poor (0%) with an average of 3.33 and a standard deviation of 0.45. Meanwhile, the percentage of daily physical education learning results in the categories very good (0%), good (0%), sufficient (20%), and needs guidance (80%) with an average of 71 and a standard deviation of 1.008. The calculated r value is 0.209 and r table 0.361, so that calculated r < r table (0.209 < 0.361) so that H0 is accepted and H1 is rejected. This shows that the level of physical fitness has no relationship with physical education learning outcomes through the physical education skill scores obtained by class XI students at MA Negeri 1 Meranti Islands.